English Teachers’ Strategies in Teaching Reading: An Interview Study - Dinda Hasri Dian Pertiwi; Elih Sutisna Yanto; Yousef Bani Ahmad (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This study aimed to determine the strategies used by English teachers at SMK Insan Tazakka, Cikampek to teach reading comprehension. This study uses two English teacher participants at different grade levels. This study employed a qualitative method of data collection. Data were collected through semi-structured interview sessions and author-administered questionnaires. Interviews were conducted with 14 questions to obtain detailed data. And a 25-item questionnaire consisting of three categories. Metacognitive strategy guidance (planning, monitoring, evaluation), cognitive strategy guidance (visualization, summarization), and social strategy guidance (collaborative learning, questioning) are performed to complete the data obtained. According to interview findings, the first English teacher used the K-W-L (Know, Want to Know, and Learned) reading strategy and SQ3R (Surveying, Questioning, Reading, Reciting, and Reviewing) strategy. This was deemed sufficient to cover all aspects of the learning process, and the K-W-L strategy allows students to practice concentration during the learning process. It is even said that the K-W-L strategy can support and help students' reading skills. At the same time, the second English teacher uses her CIRC (Cooperative Integrated Reading and Composition) teaching strategy. This is because teachers find the process easy to implement and use. The obtained questionnaire data then corroborated the previous data in writing. It can be concluded that two English teachers at SMK Insan Tazakka use different strategies in teaching reading comprehension in class.